Precise modeling of silicon carbide-based power switches - Tang, Boxuan (Nanyang Technological University, 2024)
The Silicon Carbide Metal-Oxide-Semiconductor Field-Effect Transistor (SiC MOSFET) is a new wide-bandgap semiconductor device that has high working temperature, high breakdown voltage capabilities, and low on-resistance. This paper presents an in-depth study of SiC MOSFETs and provides a detailed evaluation of their switching performance.